Clinical spectrum of females with HCCS mutation: from no clinical signs to a neonatal lethal form of the microphthalmia with linear skin defects (MLS) syndrome - Van Rahden, Vanessa A.; Rau, Isabella; Fuchs, Sigrid; Kosyna, Friederike K.; De Almeida, Hiram Larangeira; Fryssira, Helen; Isidor, Bertrand; Jauch, Anna; Joubert, Madeleine; Lachmeijer, Augusta M. A.; Zweier, Christiane; Moog, Ute; et al. (Orphanet Journal of Rare Diseases, 2014)
Segmental Xp22.2 monosomy or a heterozygous HCCS mutation is associated with the microphthalmia with linear skin defects (MLS) or MIDAS (microphthalmia, dermal aplasia, and sclerocornea) syndrome, an X-linked disorder with male lethality. HCCS encodes the holocytochrome c-type synthase involved in mitochondrial oxidative phosphorylation (OXPHOS) and programmed cell death.We characterized the X-chromosomal abnormality encompassing HCCS or an intragenic mutation in this gene in six new female patients with an MLS phenotype by cytogenetic analysis, fluorescence in situ hybridization, sequencing, and quantitative real-time PCR. The X chromosome inactivation (XCI) pattern was determined and clinical data of the patients were reviewed.Two terminal Xp deletions of >= 11.2 Mb, two submicroscopic copy number losses, one of 850 kb and one of >= 3 Mb, all covering HCCS, 1 nonsense, and one mosaic 2-bp deletion in HCCS are reported. All females had a completely (>98:2) or slightly skewed (82:18) XCI pattern. The most consistent clinical features were microphthalmia/anophthalmia and sclerocornea/corneal opacity in all patients and congenital linear skin defects in 4/6. Additional manifestations included various ocular anomalies, cardiac defects, brain imaging abnormalities, microcephaly, postnatal growth retardation, and facial dysmorphism. However, no obvious clinical sign was observed in three female carriers who were relatives of one patient.Our findings showed a wide phenotypic spectrum ranging from asymptomatic females with an HCCS mutation to patients with a neonatal lethal MLS form. Somatic mosaicism and the different ability of embryonic cells to cope with an OXPHOS defect and/or enhanced cell death upon HCCS deficiency likely underlie the great variability in phenotypes.
EVALuna2:9233